APRENDIZAGEM ORGANIZACIONAL EM SUAS DIFERENTES DIMENSÕES: A VISÃO DOS GERENTES DE UMA INDÚSTRIA FARMACÊUTICA - Silva, Elen Cristina Albuquerque (2013)
The following study aims to understand process of organizational learning (OL), as well as to how the individual and team learning contribute to it. The organizational learning may become a competitive advantage, once the organization learns faster and aims to augment its capacity through actions of performance development. Assuming a qualitative approach, the data have been collected through interviews with six workers who were responsible for sales teams in an organization which belongs to pharmaceutical market. According to the results, it was possible to notice that the organizational learning is not only a process, but also a result. In addition, it was possible to notice its importance to the development of the company s competitive advantage, as well as the relevance of the individual and team learning to the OL.